Paraoxonase 1 Activities and Lipid Parameters in Hypertension and Their Association with Chronic Alcoholism - Sudeep Kumar; Jyoti Batra; Sumesh Prasad Sah; Dinesh Kumar; Shahid Iqbal; Manisha Arora; Shivani Sharma (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To determine lipid profile, antioxidant vitamin (E and C), and malondialdehyde (MDA) levels, as well as superoxide dismutase (SOD) levels and paraoxonase 1 (PON 1) activities in alcoholic hypertensive patients.Methods: Five hundred subjects were selected for this study consisting of 250 normal healthy individuals and 250 alcoholic hypertensive subjects. Total cholesterol, triglyceride, and HDL levels were measured using the enzymatic method while the LDL and VLDL levels were calculated by Friedwald equation. The MDA level were measured using thiobarbiturate (TBA) and the Vitamin E and C were measured using the enzymatic method. The SOD and PON 1 activities were measured using phenyl acetate as the substrate.Results: Total cholesterol, triglycerides, LDL, VLDL, and MDA levels were found to be significantly high while the HDL and Vitamin E and C levels decreased among the alcoholic hypertensive subjects when compared to the control. Furthermore, significant decreases in SOD and PON 1 activities were also found among the alcoholic hypertensive subjects as compared to control.Conclusion: Alterations in lipid parameters, antioxidant vitamin levels, MDA level, SOD activities, and PON 1 activities are associated with hypertension that may be enhanced by alcohol intake, which may lead to the development cardiovascular disease.